Overcrowded Classrooms in Pesantren Musthafawiyah: Exploring the Impact of High Student Density on Female Learners in Limited Spaces - Nasution, Suryadi; Nst, Andri Muda; Hsb, Zuhdi; Pohan, Ali Jusri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study explores the impact of high classroom density on female students (santriwati) at Pesantren Musthafawiyah in North Sumatra, focusing on a population of 4,598 santriwati distributed across 77 classrooms (60 students per class). Employing a qualitative phenomenological approach, data were collected through in-depth interviews, observations, and document analysis involving 18 participants. The findings reveal three major impacts. First, overcrowded spaces cause physical and psychological discomfort, such as fatigue and difficulty concentrating, due to poor ventilation and excessive noise. Second, overcrowding erases the identity of santriwati, silencing their voices and deepening isolation within unequal gender dynamics. Third, although santriwati demonstrate resilience through strategies like self-directed learning, this resilience remains fragile, marked by declining academic performance and motivation as a result of sustained pressure. This research highlights that classroom overcrowding not only impedes learning but also threatens the well-being of santriwati, challenging the essence of inclusive Islamic education. It is recommended that reforms in facilities and classroom management be implemented to create a supportive learning environment. This study contributes new insights to the discourse on gender-based education in Islamic boarding schools (pesantren), emphasizing the urgency of structural changes for the empowerment of santriwati.